Central paroxysmal positional nystagmus: Characteristics and possible mechanisms. (2nd June 2015) - Choi, Jeong-Yoon; Kim, Ji Hyun; Kim, Hyo Jung; Glasauer, Stefan; Kim, Ji-Soo
Abstract : Objective: The diagnosis of central paroxysmal positional nystagmus (CPPN) is challenging, and the mechanisms require further elucidation. This study aimed to determine the characteristics and mechanisms of CPPN. Methods: Seventeen patients with CPPN were subjected to analyses of their clinical findings, MRI lesions, and oculographic data on spontaneous and positional nystagmus. Results: The direction of CPPN was mostly aligned with that of the head motion during the positioning, and 3 types of CPPN were identified: downbeat nystagmus on straight-head hanging, upbeat nystagmus on uprighting, and apogeotropic nystagmus during supine head roll test. The direction of CPPN was aligned with the vector sum of the rotational axes of the semicircular canals that were normally inhibited during the positioning. The intensity of evoked nystagmus was at its peak initially and then decreased exponentially over time. The time constants (TC) of the vertical CPPN ranged from 3 to 8 seconds, which corresponds to the TC of the vertical rotational vestibulo-ocular reflex. Sixteen patients (94.1%) showed more than one type of CPPN. Furthermore, persistent downbeat or apogeotropic positional nystagmus was associated in 11 patients (64.7%). Most patients with CPPN from a circumscribed brain lesion showed an involvement of the cerebellar nodulus or uvula. Conclusion: CPPN may be ascribed to enhanced responses of the vestibular afferents due to lesions involving the nodulus and uvula. CPPN could be differentiated from benign paroxysmal positional nystagmus by positional nystagmus induced in multiple planes, temporal patterns of nystagmus intensity, and associated neurologic findings suggestive of central pathologies.